Where's your creativity? - Rosen, Aaron; Watts, Riley (Tate Publishing, 2017)
PICTURE BOOKS. Where's your creativity? It's all around you! It's the tingle in your toes, or the hop in your step when you have a brand new idea. It makes you want to do something that hasn't been done before. Where's Your Creativity? is an inspirational picture book for young creatives. The fun and rhythmic text looks at ways children can express themselves creatively each day and sets imaginations alight with ideas.With bold and colourful illustrations this book explores all areas in which we can express our individual creativity, including dance, music, food and literature. Age 3+